4(2-3t)+6t=-6t-8

Simple and best practice solution for 4(2-3t)+6t=-6t-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2-3t)+6t=-6t-8 equation:


Simplifying
4(2 + -3t) + 6t = -6t + -8
(2 * 4 + -3t * 4) + 6t = -6t + -8
(8 + -12t) + 6t = -6t + -8

Combine like terms: -12t + 6t = -6t
8 + -6t = -6t + -8

Reorder the terms:
8 + -6t = -8 + -6t

Add '6t' to each side of the equation.
8 + -6t + 6t = -8 + -6t + 6t

Combine like terms: -6t + 6t = 0
8 + 0 = -8 + -6t + 6t
8 = -8 + -6t + 6t

Combine like terms: -6t + 6t = 0
8 = -8 + 0
8 = -8

Solving
8 = -8

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x^2-2x-5=2x | | x^2-2x-4=2x | | (8+y)(2y+7)=0 | | x^2-12x+38=3 | | 85=4x^2+5x+1 | | 0=-16t^2+113t+65 | | 4w^2+46w+156=0 | | 4y^2+y+15=0 | | 18y^2+9y/81y^2+18y | | 112=2w^2+6w-20 | | y=3(-2)+15 | | 2=-2x-6 | | 120=4x^2+5x+1 | | 2x+2(3x+15)=14 | | 0.59x-1.3=1.89 | | 22x+40+12x+40=794 | | 22x+40+12x+40=792 | | 22x+40+12x+40=790 | | 0.8=0.2x+3.4 | | 22x+40+12x+40=799 | | 22x+40+12x+40=818 | | 22x+40+12x+40=820 | | 22x+40+12x+40=800 | | 22x+40+12x+40=100 | | 4(-1)-4y=-41 | | 0=20w^2+6w-112 | | c=P+2b+a | | W+6/4=7 | | (2u/3v4)3 | | 1/3x^2-2x-4=0 | | (2u/3v) | | 25v^3+110v^2-75=0 |

Equations solver categories